The Teaching of Reading Skills in Arabic and English Textbooks in Iraq (Journal of the College of Basic Education, 2022)
The present paper deals with the problems of teaching reading skills as they are presented in the materials used for teaching Arabic and English in Iraqi secondary schools. The researcher finds out that those materials do not teach reading skills in the proper sense of the word which is common in the literature on the subject and he advocates some alternatives for dealing with those skills.